Risk factors for visceral Leishmaniasis among residents and migrants in Kafta-Humera, Ethiopia. - Daniel Argaw; Abate Mulugeta; Mercè Herrero; Nohelly Nombela; Tsegemariam Teklu; Teodros Tefera; Zewdu Belew; Jorge Alvar; Caryn Bern (Public Library of Science (PLoS), 2013)
BACKGROUND: Visceral leishmaniasis is a lethal parasitic disease transmitted by phlebotomine sand flies. The largest focus of VL in Ethiopia is located in the lowland region bordering Sudan, where the epidemiology is complicated by the presence of thousands of seasonal agricultural workers who live under precarious conditions. METHODOLOGY/PRINCIPAL FINDINGS: We conducted two parallel case-control studies to identify factors associated with VL risk in residents and migrants. The studies were conducted from 2009 to 2011 and included 151 resident cases and 157 migrant cases, with 2 matched controls per case. In multivariable conditional regression models, sleeping under an acacia tree at night (odds ratios (OR) 5.2 [95% confidence interval 1.7-16.4] for residents and 4.7 [1.9-12.0] for migrants), indicators of poverty and lower educational status were associated with increased risk in both populations. Strong protective effects were observed for bed net use (OR 0.24 [0.12-0.48] for net use in the rainy season among residents, OR 0.20 [0.10-0.42] for any net use among migrants). For residents, living in a house with thatch walls conferred 5-fold and sleeping on the ground 3-fold increased risk. Among migrants, the risk associated with HIV status was borderline significant and sleeping near dogs was associated with 7-fold increased risk. CONCLUSIONS/SIGNIFICANCE: Preventive strategies should focus on ways to ensure net usage, especially among migrant workers without fixed shelters. More research is needed to understand migration patterns of seasonal labourers and vector bionomics.